LEGAL ANALYSIS OF ADMINISTRATIVE LAW IN THE HANDLING OF PALM OIL PLANTATION THEFT: A CASE STUDY ON THE IMPLEMENTATION OF THE PLANTATION LAW - Loso Judijanto (CV. Adiba Aisha Amira, 2025)
This study analyses the application of administrative law in handling cases of palm oil theft, with a focus on the implementation of the Plantation Law. Through a literature review examining existing theoretical studies related to case studies, this research identifies the role of the Plantation Law in providing a clear legal basis and the challenges in its implementation in the field. The analysis results show that, although regulations are available, their implementation is often hampered by a lack of socialisation of the rules, limited public understanding, and operational challenges, such as a lack of resources for law enforcement officials. Furthermore, the study highlights the importance of collaboration between local governments, law enforcement agencies, plantation owners, and the community to enhance the effectiveness of addressing oil palm theft through legal education, technology-based surveillance, and capacity building for law enforcement agencies. This study provides practical recommendations to maximise law enforcement in the plantation sector while supporting the protection of assets for business operators.